Pengaruh Model Polya Terhadap Pemahaman Konsep Matematika Siswa Kelas V Di Sekolah Dasar - Shavero, Shanty; Fachrudin, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The Polya Model for the Comprehension of the concept of grade V students of SDN 26 Painan Selatan on the summing material and facilitating two fractions with different denominators.This type of research was quantitative research with the experimental method and quasi experiment design, with the form of Non-equivalent control group design. The sample technique used was purposive sampling technique. The data analysis technique used was the t-test. The results showed that the average of post-test in experiment class was 70.3 and the average in control class was 46.1. Analysis of t-test both in experiment and control classes was obtained tcount = 2.33 and ttable = 2.04 at a significant level of 0.05. Hence tcount > ttable then ha was accepted. Thus it can be concluded that the method of the polya model problem solving method positively answers the students' understanding of grade V SDN 26 Painan Selatan on addition and solving fractions with different denominators